The house of competence of the quality manager - Helgi Þór Ingason; Elín Ragnhildur Jónsdóttir (Cogent Business & Management, 2017)
In modern organizations the work of the quality manager is varied and complex. Therefore, what common attributes should characterize an exemplary quality manager? A conceptual model has been developed, entitled The House of Competence of the Quality Manager. The model presents important different attributes for the role of quality manager. This model can be used by quality managers who wish to broaden their understanding of the competence needed in their work and to define their profession. The model was developed through a four-step approach, beginning with a review of the rather scarce literature on the necessary attributes of a quality manager. This was followed by work in a small focus group of quality practitioners, which led to a survey questionnaire being sent out to a larger group of professional quality managers in Iceland. The final step was the classification of the attributes as knowledge, skills, or competence. The results of this survey give a good indication of what attributes are desirable and their relative importance.
Keywords: 650